Iodide-induced shuttling of a halogen- and hydrogen-bonding two-station rotaxane. - Caballero, A; Swan, L; Zapata, F; Beer, P (Wiley, 2014)
The first example of utilizing halogen-bonding anion recognition to facilitate molecular motion in an interlocked structure is described. A halogen-bonding and hydrogen-bonding bistable rotaxane is prepared and demonstrated to undergo shuttling of the macrocycle component from the hydrogen-bonding station to the halogen-bonding station upon iodide recognition. In contrast, chloride-anion binding reinforces the macrocycle to reside at the hydrogen-bonding station.